22 Implementation of a pharmacist-driven antimicrobial time-out for medical-surgery services in an academic pediatric hospital. (2nd December 2020) - Stang, Christopher; Tansmore, Jessica; Parson, Katelyn; Nuss, Kathryn; Sapko, Matthew; Thompson, Zachary; Buckingham, Don; Abdel-Rasoul, Mahmoud; Watson, Joshua; Jaggi, Preeti
Abstract : Background: This quality improvement initiative implemented a pharmacist-driven antimicrobial time-out (ATO) in a large, free-standing pediatric hospital. Objectives: Our goal was to complete and document an ATO for 90% of eligible patients hospitalized on general pediatric medicine or surgery services within 12 months. Methods: A multidisciplinary quality improvement team developed an ATO process and electronic documentation tool. Clinical pharmacists were responsible to initiate and document an ATO for pediatric medicine or surgery patients on or before the 5th calendar day of therapy. Interventions included education of pharmacists and physicians, as well as ATO audit and feedback to the pharmacists. We used statistical process control methods to track monthly rates of ATO completion from October 2017 through April 2019. Results: Among 647 eligible antimicrobial courses over the 17-month study period, the mean monthly documentation rate increased from 54.6% to 83.5% (p < 0.001) (figure 1 ). The mean ATO documentation rate increased from 32.8% to 74.2% (p < 0.001) for the pediatric medicine service and from 65.0% to 88.1% for the pediatric surgery service (p = 0.006). Among 302 notes assessed for quality, 35.8% had all the required data fields completed. A tentative antimicrobial stop date was the data element completed least often (49.3%) (tables 1 and 2 ). Conclusions: We successfully implemented a pharmacist-driven ATO, highlighting the opportunity for pharmacists to play an active role in antimicrobial stewardship. Defining treatment duration remains an important antimicrobial stewardship target.